Antifungal Immunological Defenses in Newborns - Michalski, Christina; Kan, Bernard; Lavoie, Pascal M. (Frontiers in Immunology, 2017)
Newborns are prone to fungal infections, largely due to Candida species. The immunological basis for this vulnerability is not yet fully understood. However, useful insights can be gained from the knowledge of the maturation of immune pathways during ontogeny, particularly when placed in context with how rare genetic mutations in humans predispose to fungal diseases. In this article, we review these most current data on immune functions in human newborns, highlighting pathways most relevant to the response to Candida. While discussing these data, we propose a framework of why deficiencies in these pathways make newborns particularly vulnerable to this opportunistic pathogen.